Model of teaching factory in vocational high school fashion program students - ampera, dina; Tanjung, Nurhayati; farihah, farihah; Sinukaban, Veronika Yulisna; Juliana, Netty (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
The Fashion Design expertise program applies a teaching factory learning system to productive subjects, including Industrial Clothing. Judging from the planning and implementation, the teaching factory learning model in this subject has not run optimally. This study aims to: to determine the effectiveness of the teaching factory model for students of fashion as a learning model at State Vocational High School 1 Beringin. This type of research is descriptive qualitative with research and development methods. This research was conducted at State Vocational High School 1 Beringin, with the research subjects being teachers and students of the Fashion Design Expertise Program. The object of this research is teaching factory activities in productive subjects. Research on the development of the Teaching Factory learning model went through three stages, namely: 1) Needs analysis, 2) Product development, and 3) Expert Validation. The results of this study indicate that the Teaching Factory model has been effectively used in productive subjects such as industrial clothing with an assessment of 98.6% by material experts and 88% by design experts. After going through the validation stage by material experts and design experts, it can be concluded that the Teaching Factory learning model product developed has been effectively used as a learning model in productive subjects for students of the Dressmaking Expertise Program at Beringin 1 State Vocational High School